Faktor Yang Berhubungan Dengan Penggunaan TOGA (Tanaman Obat Keluarga) Dalam Meningkatkan Kesehatan Masyarakat Di Pagatan Kecamatan Kusan Hilir - Miftahul Jannah; Melviani Melviani; Sarkiah Sarkiah (LPPM Universitas Sari Mulia, 2021)
Introduction: Health is one of the most important things for humans, one of which is doing self-medication at home with natural ingredients or made from nature. The use of TOGA is due to the high level of public awareness of health and the increasing knowledge of TOGA from each individual in the community. Purpose : The purpose of this study was to determine the factors associated with the use of Family Medicinal Plants (TOGA) in the Pagatan community. Methods: The method used in this research is using the Cross Sectional method. Sampling using the consective sampling method with data analysis of the p-Value value generated after being entered into SPPS using the Chi-Square method. Results: The results obtained can be seen from 50 respondents there are 36 people who use TOGA. Variables related to the use of TOGA in improving public health were age (p = 0.040) and income (p = 0.028), and those that were not related were education (p = 0.725) and information (p = 0.865). Conclusion: The results showed that there were 2 related factors, namely age and income, while education and information had no relationship.